Development of software and methodological support for an online platform for independent fitness training for master's students at physical education universities - Saykina, E.G.; Dityatin, A.N.; Eydelman, L.N.; Smirnova, Yu.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop an innovative teaching model that combines traditional and distance learning formats to optimise students' independent work and to justify the effectiveness of the software and methodological complex for the online platform. Methods and structure of the study. The online platform and its software and methodological support were developed for the purpose of independent work by master's students studying in the field of 44.04.01 ‘Pedagogical Education’, specialising in ‘Fitness Technologies in Physical Culture’ and ‘Fitness Management in Physical Education’. Results and conclusions. Requirements and methodological recommendations for the development of the online platform have been formulated, and its potential applications in the educational process for master's students have been revealed. Its role and effectiveness in the formation of professional competencies and practical skills when completing independent work assignments in the academic disciplines of this specialisation have been determined.